A Twin Transition or a policy flagship? Emergent constellations and dominant blocks in green and digital technologies - Linnea Nelli; Maria Enrica Virgillito; Marco Vivarelli (Global Labor Organization (GLO), 2025)
The aim of this paper is to understand whether what has been labelled as "twin transition", at first as a policy flagship, endogenously emerges as a new technological trajectory stemming by the convergence of the green and digital technologies. Embracing an evolutionary approach to technology, we first identify the set of relevant technologies defined as "green", analyse their evolution in terms of dominant blocks within the green technologies and concurrences with digital technologies, drawing on 560,720 granted patents by the US Patent Office from 1976 to 2024. Three dominant blocks emerge as relevant in defining the direction of innovative efforts, namely energy, transport and production processes. We assess the technological concentration and underlying complexity of the dominant blocks and construct counterfactual scenarios. We hardly find evidence of patterns of actual endogenous convergence of green and digital technologies in the period under analysis. On the whole, for the time being, the "twin transition" appears to be just a policy flagship, rather than an actual endogenous technological trajectory driving structural change.
Keywords: O33; Q55; Q58; 330; Twin transition; policy flagship; technological trajectories